Dyslipidemia and the Risk of Developing Hypertension in a Working‐Age Male Population - Otsuka, Toshiaki; Takada, Hirotaka; Nishiyama, Yasuhiro; Kodani, Eitaro; Saiki, Yoshiyuki; Kato, Katsuhito; Kawada, Tomoyuki (Journal of the American Heart Association, 2016)
Background Hypertension is one of the main comorbidities associated with dyslipidemia. This study aimed to examine the extent to which dyslipidemia increases the risk of developing hypertension in a Japanese working‐age male population. Methods and Results We analyzed data from 14 215 nonhypertensive male workers (age 38±9 years) who underwent annual medical checkups. Subjects were followed up for a median of 4 years to determine new‐onset hypertension, defined as blood pressure (BP) ≥140/90 mm Hg or use of antihypertensive medication. The associations between serum lipid levels and development of hypertension were examined. During the follow‐up period, 1483 subjects developed hypertension. After adjusting for age, body mass index, impaired fasting glucose/diabetes, baseline BP category, alcohol intake, smoking, exercise, and parental history of hypertension, subjects with a total cholesterol (TC) level ≥222 mg/dL were at a significantly increased risk of developing hypertension (hazard ratio: 1.28; 95% CI: 1.06–1.56) compared to subjects with a TC level ≤167 mg/dL. Similar results were observed for subjects with high low‐density lipoprotein cholesterol (LDLC) and non‐high‐density lipoprotein cholesterol (HDLC) levels. A U‐shaped relationship was found between HDLC level and risk of hypertension; compared to the third quintile, the multiadjusted hazard ratio was 1.22 (95% CI: 1.03–1.43) in the lowest quintile and 1.34 (95% CI: 1.12–1.60) in the highest quintile. Conclusions Elevated serum levels of TC, LDLC, and non‐HDLC were associated with an increased risk of hypertension in working‐age Japanese men. For HDLC, risk of hypertension was increased at both low and high levels.